Differentiation of symbiotic bacteria is a new evidence for two genetic clades of Aphelinus mali (Hymenoptera: Aphelinidae) in China. (1st October 2020) - Du, Min; Yu, Jianing; Zhou, Yunjiao; Wang, Xueying; Ma, Tiantian; Tan, Xiumei; Wan, Fanghao; Zhou, Hongxu
ABSTRACT: Aphelinus mali is an important endoparasitoid of Eriosoma lanigerum (Hausmann) (Hemiptera: Aphididae). In our previous study, A. mali in China was divided into two genetic clades, named the Shandong and Liaoning clades, which showed differences in both biological characteristics and the level of pest control. The purpose of this study was to analyse the diversity of endosymbiotic bacteria associated with the two clades. An Illumina HiSeq sequencing platform was used to measure the 16s V3-V4 hypervariable region sequences of 15 A. mali samples from five regions in China. Based on clustering of OTUs, species annotation, abundance analysis and constructing phylogenetic trees, the structural differences of symbiotic bacterial species in different regions and samples were revealed. Our results showed QHD population had different patterns of endosymbiont diversity. The sample cluster analysis showed that there was low species richness in QHD, and proteobacteria accounted for more than 90%, significantly different from other four regions. It suggested this population was a separate re-invasion or is evidence for genetically distinct clades of A. mali . We hold the opinion that the differentiation of the symbiotic bacteria could be a new evidence of the two genetic clades of A. mali . Abbreviations: Aphelinus mali - A. mail Eriosoma lanigerum - E. lanigerum Shandong - SD Liaoning - LN Tai'an - TA Qingdao - QD Liaocheng - LC Zhaotong - ZT Qinghunagdao - QHD Operational taxonomic unit - OUT Unweighted pair-group method with arithmetic means - UPGMA Non-Metric Multi-Dimensional Scaling - NMDS